Headache: A primary indicator for depression in out patient department at a teritiary care hospital (Panacea Journal of Medical Sciences, 2024)
Background: Headache is a very frequently reported complaint in psychiatric out patient department which is the most neglected symptom in now a days hectic life scenario until and unless it will not hampers the daily routine activities of a human being. Both Headache and low mood are very common but still the frequency of patients attending an outpatient department is far lesser for depression compared to headache whereas Headache is quite a very common presenting complaint reported by the patients.Materials and Methods: 100 patients presenting with chief complaints of headache were taken from Psychiatric outpatient department of Maharishi Devraha Baba Autonomous State Medical College from august 2022 to november2022. All patients were assessed for routine pathological blood investigation, psychological testing mental status examination and clinical examination.Results: On testing questionnaire on all 100 patients who were taken in this study all of them shows symptoms that fulfils the criteria for Depression 5% of the patients exhibits mild Depression,12%of the patients shows borderline Depression,70% of the patients shows moderate Depression whereas 8% of the patients shows severe Depression.Conclusion: This study emphasizes the importance of accurate diagnosis of depression, emphasizing the need for proper analysis of patient complaints, particularly headaches, to prevent misdiagnosis.